Regional Exposure to Air Pollution and Health Behaviors as a Risk Factor for Suicide Attempt: The Seventh Korean National Health and Nutrition Examination Survey (KNHANES), 2016-2017, Korea Centers for Disease Control and Prevention (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study is to identify the influencing factors of fine particleconcentration levelby region and health behaviors on suicide attempts.Method/Statistical Analysis: This study used the 7th (2016-2017) primitive data disclosed by the NationalHealth Nutrition Examination Survey. Considering the design features of the sample data, it is analyzed witha complex sampling method by reflecting stratas, clusters, and weight. The data were analyzed using logisticregression analysis of the complex sampleusing the SPSS/WIN 18.0 program.Findings: As a result of logistic regression analysis, the provability of suicide attempt was 12.32 times(95% CI 5.33-28.49, p